9514 1404 393
Answer:
(x, y) = (3, 12)
Step-by-step explanation:
Using the given variable definitions, we can write the equations ...
y = x + 9
2(x +y) = 30
__
Solving the second equation for y, we have ...
y = 15 -x
Substituting this into the first equation gives ...
15 -x = x +9
6 = 2x . . . . . . . . . add x-9
3 = x . . . . . . . . . . divide by 2
y = 3+9 = 12 . . . . substitute into the first equation
The numbers are (x, y) = (3, 12).
I think the answer would be x= 4/7 y = +-16/7
Answer:
I would help you and say the answer but..
Step-by-step explanation:
I dont know what it is :c